Agama Dalam Pembentukan Struktur Sosial Masyarakat Sidoarjo : The Religion in the Formation of Social Structure of Sidoarjo Society - Cindy Wahyu (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2025)
The existence of religion is important in the daily life of humans as social beings, both in this world and in the next. Religious teachings influence the way people understand each other. Religion is present in human life to provide social glue, strengthen family relationships and create peace and do many other things to maintain social stability. The purpose of this research is to identify how religion affects the formation of social layers, such as how religion affects social status, power sharing and economic impact. In this research, the method used is a qualitative method and uses an ethnographic study approach, the ethnographic method is used to find out how religion shapes the social structure in Sidoarjo. The results show the significant role of religion in shaping the social structure of society in Sidoarjo. Through regular recitations, social activities at mosques and religious celebrations, religion strengthens solidarity and cohesion among residents. Mosques and other religious institutions serve as the main centers of social interaction, not only in the spiritual dimension but also in aspects of daily social interaction. Religion provides values and norms that direct people's behavior, as well as assisting in the formation of social identity and maintaining order in the community. The role of religious institutions in providing solutions to social changes induced by modern technology and globalization.